The ability of isoinertial assessment to monitor specific training effects - Jidovtseff, B.; Croisier, J.-L.; Scimar, N.; Demoulin, C.; Maquet, D.; Crielaard, J.-M. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim. The aim of this study was to investigate the ability of isoinertial assessment to monitor training effects. Both parametric and curve analysis of the results were used to underline the specificity of maximal strength and maximal velocity resistance training methods. Methods. Twenty-four untrained subjects were randomly assigned into three groups: a maximal strength-training group (heavy loads: 80% to 98% of the one repetition maximum [1-RM]), a maximal velocity-training group (light loads: 25% to 50% of 1-RM) and a control group. All the subjects were tested in bench press exercises before and after the 6-week training period. An isoinertial dynamometer was used to assess velocity and power at four increasing loads: 35%, 50%, 70% and 95% of the 1-RM load. Post-test protocol also included a trial at 105% of the 1-RM load. Results. Isoinertial assessment demonstrated for both training groups significant gains at each load. Some specific adaptations appeared: strength training presented a greater increase for average power (+49%, P<0.001) and average velocity (+48%, P<0.001) at 95% of 1-RM, while velocity training emerged as a more effective way to improve performance at 35% and 50% of 1-RM (+11 to 22%) in comparison with strength training (+7 to 12%). The analysis of power and velocity curves specified that strength training enhanced performance earlier in the movement, while velocity training extended the propulsive action at the end of movement. Conclusion. The original combination of parametric and curve isoinertial assessment appears to be a relevant method for monitoring specific training effects. The complementarity of both strength and velocity training programmes underlined in this study could lead to practical applications in profiling training programmes.